PHYSICAL QUALITY OF FRESH, CHILLED, AND FROZEN BALI BEEF - C.A., Moniaga; Sriyani, N. L. P.; Sumardani, N. L. G. (Jurnal Peternakan Tropika; Vol 11 No 2 (2023): Vol. 11 No. 2 Tahun 2023; May - August, 2023)
This study aims to understand the physical quality of fresh, chilled, and frozen bali beef which was reviewed from the objective test including; color, meat pH, water holding capacity (WHC), cooking loss, and drip loss. This study used a completely randomized design (CRD) in a unidirectional pattern of 3x7 with 3 treatments of bali beef, namely: (1) meat stored at room temperature (27°C to 35°C) for less than 1 day (fresh meat), (2) meat stored at 0°C to 4°C with a storage period of 2 days (chilled meat), (3) meat with storage at - 20°C to - 47°C with a storage time of 2 days (frozen meat). The results showed that the physical quality of fresh bali beef was better than the physical quality of chilled and frozen bali beef on the variables of meat pH, water holding capacity (WHC), cooking loss and drip loss. For the color variable, the color of fresh meat was not significantly different from the chilled meat but significantly different from the frozen meat. For the water holding capacity variable, the physical quality of cold meat was not significantly different from that of frozen meat. In addition to these two variables, it can be concluded that the physical quality of Bali beef has decreased significantly with the best order being Bali beef in fresh condition, then Bali beef in chilled condition, and Bali beef in frozen condition. Keywords: Physical quality, bali beef, fresh meat, chilled meat, frozen meat